First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Laboratory observations of continuous and intermittent subharmonic edge waves - Xuelin Ding; Roland Garnier; Colin Whittaker; Pablo Blondeaux; Giovanna Vittori; Robert A. Dalrymple; Pedro Lomonaco; R.T. Guza; Giovanni Coco (Coastal Engineering, 2025)

Evaluating five shoreline change models against 40 years of field survey data at an embayed sandy beach - Oxana Repina; Rafael C. Carvalho; Giovanni Coco; José A.Á. Antolínez; Iñaki de Santiago; Mitchell D. Harley; Camilo Jaramillo; Kristen D. Splinter; Sean Vitousek; Colin D. Woodroffe (Coastal Engineering, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The interaction between vegetation patchiness and tidal flows in a shortleaf seagrass meadow - Tiago D. da Silva; Julia C. Mullarney; Conrad A. Pilditch; Giovanni Coco (Limnology and Oceanography, 2024)
Seagrasses are critical coastal habitats that provide numerous ecosystem services. The inherent patchiness within meadows exerts a significant influence on the flow‐vegetation interaction, which, in turn, affects the array of services provided by these environments. We present field observations of vegetation distribution and hydrodynamic measurements within and surrounding an approximately 2 m diameter gap (bare sediment) in a fragmented seagrass meadow. We show that variability in mean flows and turbulence is correlated with meadow structure at small (O (10 0 m)) and large (O (10 2 m)) spatial scales. Our observations reveal that bare gaps within seagrass meadows lead to faster flows and lower bed elevations. Despite slower flow speeds above the dense seagrass adjacent to the gap, the rates of dissipation of turbulent energy above the vegetation are typically around an order of magnitude larger than above the bare bed. Associated with this enhanced dissipation of turbulent energy, we observed a dominance of down‐deceleration events promoting fluid exchange and mixing and driving mass flux into the canopy. Analysis of directional variograms demonstrates that the major continuity axis within NDVI (normalized difference vegetation index) imagery (used as a proxy for vegetation biomass) coincides with the major axis of flow on both gap and meadow scales. Conversely, along the axis of minor flow variance, vegetation remains dense and exhibits greater uniformity. These findings indicate a feedback mechanism between seagrass meadow patchiness and spatial structure through flow modification, which may be beneficial for plant development.

Polyester microfiber impacts on coastal sediment organic matter consumption - Samantha M. Ladewig; Thomas S. Bianchi; Giovanni Coco; Eliana Ferretti; Rebecca V. Gladstone-Gallagher; Jenny Hillman; Julie A. Hope; Candida Savage; Stefano Schenone; Simon F. Thrush (Marine Pollution Bulletin, 2024)

On the projected changes in New Zealand's wave climate and its main drivers - João Albuquerque; Jose A. A. Antolínez; Fernando J. Méndez; Giovanni Coco (New Zealand Journal of Marine and Freshwater Research, 2024)
Wave climatologies from historical and projected simulations of the ACCESS1.0, MIROC5 and CNRM‐CM5 Global Circulation Models (GCM) were sourced from the Coordinated Ocean Wave Climate Project (COWCLIP) and downscaled using the SWAN wave model. Biases between GCM's historical simulations and a regional hindcast were assessed, and the two best‐performing models (ACCESS1.0, MIROC5) had their projections analysed. A general increase in wave height and period was observed along the south/west, together with a decrease in along the north/east coasts. The projected near‐term (NEA21C) period shows mostly a increase, whilst for the long‐term (END21C) period, increased and decreased are present. The areas of statistically significant changes are larger in the END21C than in the NEA21C period. The wave direction change is counter‐clockwise along the west and clockwise along the east coasts. This study is a first assessment of historical and projected GCM‐forced waves along New Zealand and the database we generated can be of great value for renewable energy research, risk assessment and the mitigation of future coastal hazards.

A regional analysis of tide-surge interactions during extreme water levels in complex coastal systems of Aotearoa New Zealand - Wagner Costa; Karin R. Bryan; Scott A. Stephens; Giovanni Coco (Frontiers in Marine Science, 2023)
Tide-surge interaction (TSI) is a critical factor in assessing flooding in shallow coastal systems, particularly in estuaries and harbours. Non-linear interactions between tides and surges can occur due to the water depth and bed friction. Global investigations have been conducted to examine TSI, but its occurrence and impact on water levels in Aotearoa New Zealand (NZ) have not been extensively studied. Water level observations from 36 tide gauges across the diverse coast of NZ were analysed to determine the occurrence and location of TSI. Statistical analysis and numerical modelling were conducted on data from both inside and outside estuaries, focusing on one estuary (Manukau Harbour) to determine the impact of TSI and estuarine morphology on the co-occurrence rate of extreme events. TSI was found to occur at most sites in NZ and primarily affects the timing of the largest surges relative to high tide. There were no regional patterns associated with the tide, non-tidal residual, or skew-surge regimes. The strongest TSI occurred in inner estuarine locations and was correlated with the intertidal area. The magnitude of the TSI varied depending on the method used, ranging from -16 cm to +27 cm. Co-occurrence rates of extreme water levels outside and inside the same estuary varied from 20% to 84%, with TSI modulating the rate by affecting tidal amplification. The results highlight the importance of investing in a more extensive tide gauge network to provide longer observations in highly populated estuarine coastlines. The incorporation of TSI in flooding hazard projections would benefit from more accurate and detailed observations, particularly in estuaries with high morphological complexity. TSI occurs in most sites along the coast of NZ and has a significant impact on water levels in inner estuarine locations. TSI modulates the co-occurrence rate of extreme water levels in estuaries of NZ by affecting tidal amplification. Therefore, further investment in the tide gauge network is needed to provide more accurate observations to incorporate TSI in flooding hazard projections.

Pigmented cereals and legume grains as healthier alternatives for brewing beers - Giuseppe Romano; Maria Tufariello; Nadia Calabriso; Laura Del Coco; Francesco P. Fanizzi; Antonio Blanco; Maria A. Carluccio; Francesco Grieco; Barbara Laddomada (Food Bioscience, 2023)

Real-world impacts of microplastic pollution on seafloor ecosystem function - Samantha M. Ladewig; Giovanni Coco; Julie A. Hope; Amanda M. Vieillard; Simon F. Thrush (Science of The Total Environment, 2023)

In vitro antioxidant and wound healing properties of baru nut extract ( Dipteryx alata Vog.) in pulmonary epithelial cells for therapeutic application in chronic pulmonary obstructive disease (COPD) - Julia Cedran Coco; Janaína Artem Ataide; Johannes A. Sake; Elias Basile Tambourgi; Carsten Ehrhardt; Priscila Gava Mazzola (Natural Product Research, 2022)

Recreational angling and spearfishing on social media: insights on harvesting patterns, social engagement and sentiments related to the distributional range shift of a marine invasive species - Valerio Sbragaglia; Lucía Espasandín; Salvatore Coco; Alberto Felici; Ricardo A. Correia; Marta Coll; Robert Arlinghaus (Reviews in Fish Biology and Fisheries, 2022)

Historical and future storm surge around New Zealand: From the 19th century to the end of the 21st century - Laura Cagigal; Ana Rueda; Sonia Castanedo; Alba Cid; Jorge Perez; Scott A. Stephens; Giovanni Coco; Fernando J. Méndez (International Journal of Climatology, 2020)
We developed a new hindcast for storm surge at a 0.25° spatial scale for the whole New Zealand area using a statistical downscaling technique that links the mean local atmospheric conditions with the maximum storm surge levels at a daily scale. After validating the hindcast against sea level instrumental records from 17 tidal gauges around New Zealand, the same technique has been applied to obtain storm surge projections until 2,100 using different global climate models. The global climate models have been previously classified according to their ability to reproduce the past climatology in the studied area and seven models have been selected in order to explore their effect on storm surge projections. For the two representative Concentration Pathways studied, the projections indicate that the storm surge associated with the 50 years return period will increase in magnitude in the Southern areas while it will decrease in the Northern region. Even where a decreasing linear trend over the annual maxima is observed in the future time series, sporadic events of higher magnitude than the historical peaks can be.

A Systematic Review of Neurocognitive Functioning in Behçet’s Disease - Caroline A. Fisher; Coco Bernard (Neuropsychology Review, 2019)

Detecting spiny dogfish in grey seal diets - Kathryn A. Ono; Cathleen M. Steinbeiser; Austin B. Coco; Matthew J. Sheehan; Abigail J. Beck; Michelle N. Dufault; Katelyn M. Gilbert; Jessica J. Antonez; Zachary H. Olson (Conservation Genetics Resources, 2019)

The heating of substrates beneath basaltic lava flows - Sophia W. R. Tsang; Jan M. Lindsay; Giovanni Coco; Robert Wysocki; Geoffrey A. Lerner; Erika Rader; Gillian M. Turner; Ben Kennedy (Bulletin of Volcanology, 2019)

Marine climate variability based on weather patterns for a complicated island setting: The New Zealand case - Ana Rueda; Laura Cagigal; Jose A. A. Antolínez; Joao C. Albuquerque; Sonia Castanedo; Giovanni Coco; Fernando J. Méndez (International Journal of Climatology, 2019)
Understanding marine climate variability is important for coastal planning and marine operations. It is also particularly challenging for complicated settings (e.g., islands) and data‐poor regions. The aim of this work is to establish a relationship between daily synoptic atmospheric patterns, and wave and storm surge conditions around New Zealand waters, based on instrumental and reanalysis data. The daily predictor we developed is able to represent sea and swell wave conditions as well as storm surge variability over different temporal scales. However, when climate variability is analysed on a longer temporal period, based on the 20th century reanalysis, large inhomogeneities are found. This highlights the dangers related to assessing climate variability, especially in data‐poor regions (such as New Zealand), where inhomogeneities could be interpreted as actual changes.

Particulate air pollution from wildfires in the Western US under climate change - Jia Coco Liu; Loretta J. Mickley; Melissa P. Sulprizio; Francesca Dominici; Xu Yue; Keita Ebisu; Georgiana Brooke Anderson; Rafi F. A. Khan; Mercedes A. Bravo; Michelle L. Bell (Climatic Change, 2016)

Authority in Arctic governance: changing spheres of authority in Greenlandic offshore oil and gas developments - Coco C. A. Smits; Jan P. M. van Tatenhove; Judith van Leeuwen (International Environmental Agreements: Politics, Law and Economics, 2014)

Trypanocidal and cytotoxic evaluation of synthesized thiosemicarbazones as potential drug leads against sleeping sickness - Bienvenu Glinma; Sika D. S. Kpoviessi; Fernand A. Gbaguidi; Coco N. Kapanda; Joanne Bero; Joëlle Quetin-Leclercq; Mansourou Moudachirou; Jacques Poupaert; Georges C. Accrombessi; Emma W. Gachomo; Lamine Baba-Moussa; Simeon O. Kotchoni (Molecular Biology Reports, 2014)

Environmental drivers of demographics, habitat use, and behavior during a post-Pleistocene radiation of Bahamas mosquitofish (Gambusia hubbsi) - Justa L. Heinen; Matthew W. Coco; Maurice S. Marcuard; Danielle N. White; M. Nils Peterson; Ryan A. Martin; R. Brian Langerhans (Evolutionary Ecology, 2013)

Soybean chlorotic spot virus, a novel begomovirus infecting soybean in Brazil - Daniela Coco; Iara P. Calil; Otavio J. B. Brustolini; Anesia A. Santos; Alice K. Inoue-Nagata; Elizabeth P. B. Fontes (Archives of Virology, 2013)

Is cocaine a social drug? Exploration of the stereo-structure of cocaine’s pharmacophore - Jacques H. Poupaert; Fernand A. Gbaguidi; Coco N. Kapanda; Hocine Aichaoui; Christopher R. McCurdy (Medicinal Chemistry Research, 2013)

Evidence for genetic epistasis in human insulin resistance: the combined effect of PC-1 (K121Q) and PPAR?2 (P12A) polymorphisms - R. Baratta; R. Di Paola; D. Spampinato; G. Fini; A. Marucci; A. Coco; R. Vigneri; L. Frittitta; V. Trischitta (Journal of Molecular Medicine, 2003)